Penentuan Pusat-Pusat Pertumbuhan Untuk Pengembangan Wilayah Hinterland Kota Banjarbaru - Bayu Ponco Purnawirawan; Nasruddin Nasruddin (Universitas Negeri Gorontalo, 2025)
Regional development disparities remain a major issue in regional development planning, particularly in cities that are experiencing rapid growth and play a strategic role as regional hubs. Banjarbaru City, with its increasingly important position in the urban system of South Kalimantan, needs to identify growth centers in order to direct the development of its hinterland in a more structured and sustainable manner. This study aims to identify subdistricts with the potential to become growth centers and analyze the strength of interactions between subdistricts in Banjarbaru City. The research method used is a quantitative approach with census and survey techniques, through scalogram analysis, centrality index, and gravity model. The results show that the subdistricts of North Banjarbaru, South Banjarbaru, and Landasan Ulin have the most complete facilities and the highest centrality index, thus serving as the main growth centers. The subdistrict of Cempaka functions as a secondary growth center, while the subdistrict of Liang Anggang serves as the hinterland. Gravity analysis shows that the strongest spatial interaction occurs between the main growth centers, while the relationship between the center and the hinterland shows varying levels of interaction influenced by distance and population. These findings emphasize the importance of strengthening connectivity and equal distribution of facilities to encourage the spread of development in Banjarbaru City.